Oral Rehabilitation with Implant‐Retained Overdenture in a Patient with Down Syndrome. Issue 2 (24th January 2017) - Altintas, Nuray Yilmaz; Kilic, Serdar; Altintas, Subutay Han
Abstract: Down syndrome, known as trisomy 21, is the most common chromosomal disorder. The disorder affects mental and systemic development as well as oral structure, including dental anomalies, high susceptibility of periodontal disease, and poor quality of alveolar bone. This report presents a case of dental rehabilitation by means of dental implants of a patient with Down syndrome. Two titanium dental implants were placed in the maxilla, and three titanium dental implants were installed in the mandible. One implant was lost during the osseointegration period. The prosthetic rehabilitation was performed with implant‐retained maxillary and mandibular overdentures with the Locator attachment system. After a 2‐year follow‐up period, the patient was doing well, and all implants were clinically stable with no signs of bone loss or inflammation. The present study emphasizes that implant‐retained overdentures with Locator attachment system could be a therapeutic option even for patients with Down syndrome. This therapy prevents crestal bone loss around the implants, improves functional and esthetic outcomes, and provides optimum oral hygiene for patients with mild mental impairment. Careful patient selection and education of patients and caregivers are essential considerations for a successful and safe treatment with dental implants in Down syndrome patients.